Baseline survey of Narsingdi, vol II : income, assets and agriculture - Bangladesh Rural Advancement Committee (Dacca, Bangladesh : Research and Evaluation Division, Bangladesh Rural Advancement Committee, 1982)
Socioeconomic and demographic profile of the rural poor in Narsingdi Thana, Bangladesh.
Vol. 2 has title: Narsingdi baseline survey.
Includes bibliographies and statistical tables.
Keywords: BRAC (Bangladesh Rural Advancement Committee)